PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS TUNANETRA MELALUI METODE TASMI’ (TALQIN), TAFAHUM, TIKRAR DAN MUROJAAH SEKOLAH LUAR BIASA MAHARANI - Exlis Adibah Silvia Risma (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
This article examines the learning of blind children with special needs in memorizing the Al-Qur’an using the tasmi’ (talqin), tafahum, tikrar and murojaah (3t 1m) methods at maharani SLB. This 3t 1m method is an effective method and suitable for children learning tahfidz Al-Qur’an, including children with visual impairments. The purpose of this research is to explain the purpose of this study is to explain the steps for using the 3t 1m method and realizing the tahfidz Al-Qur’an program with the 3t 1m method. The method used in this research is filed research with a qualititative descriptive approach. The result obtained in memorizing with the 3t 1m method are an increase in children’s memorization of the Al-Qur’an